A review of malarial retinopathy in severe malaria - H. L. Sithole (African Vision and Eye Health, 2011)
The ocular manifestations of severe malaria in patients with cerebral malaria (CM) include retinal whitening, vessel discolouration, retinal haemorrhages and papilloedema. A large prospective study of Malawian children with CM found that the severity of retinal signs, including the number of retinal haemorrhages, was related to the outcome and length of coma in survivors of malaria. In a smaller number of Kenyan children with cerebral malaria, retinal haemorrhages were associated with deep coma and severe anaemia. A study on the effect of malarial retinopathy on vision found no detectable effect on visual acuity (VA) but where malaria isaggravated by failure to receive treatment this may possibly affect VA. The failure to receive treatment may be directly linked to the socio-economic status (SES) of those affected and this may occur in the KwaZulu-Natal, Mpumalanga and Limpopo provinces of South Africa where malaria is endemic. This suggests the need for effective health education and health promotion amongst those affected by malaria especially in severely affected provinces of South Africa. Also, in view of the direct ocular consequences of severe malaria, optometrists should engage communities in health education and health promotion. This is particularly relevant because in some communities, a large majority of those suffering from malarial infections do not visit formal health facilities for treatment. In so doing, optometrists in South Africa will be contributing positively to the Millennium Development Goals which seek, amongst others, to reduce unwarranted sources of morbidity worldwide. (S Afr Optom 2011 70(3) 129-135)